PENGARUH STRUKTUR ORGANISASI TERHADAP KINERJA PEGAWAI PADA PT KRUGER VENTILATION INDONESIA - Andhika Hemas Ramadhan; Pramudya, Angga Putra; Fatiha, Ilha Hafilda; Pangaribuan, Khairurrahmi (Journal of Business Education and Social, 2024)
Achieving predetermined organizational goals is largely determined by human performance factors and existing systems, so it is necessary to establish an organizational structure with a clear division of work. The phenomenon that occurs in carrying out work activities is that not all employees are usually aware of the importance of their roles and responsibilities towards the organization. From the description of the background to the problem above, the author will analyze whether there is an influence of the organizational structure at PT Kruger Ventilation Indonesia on employee performance. The research method used is qualitative where the researcher conducted an interview with one of the heads of production and looked for sources through books, articles and journals. This research aims to determine the influence of Organizational Structure variables on Employee Performance and the conclusion of this research is that the application of job specialization, Departmentalization, Chain of Command, Span of Control, Centralization/Decentralization and Formalization, in organizational structure has a strong influence on PT Kruger Ventilation Employee Performance Indonesia.